Durability of woven composite structures - Satrio Wicaksono (2014)
The current study focuses on the durability of the composite structures, especially structures that are made of woven carbon-epoxy. The fatigue behaviour of woven composite structures is different from the fatigue behaviour of structures made of unidirectional (UD) and multidirectional (MD) composites. The fatigue behaviour of woven composites is much more complex then UD and MD composites because the interaction between warp and fill zone need to be taken into account. Thus, a thorough study on fatigue behaviour of woven composites is very important and much needed at this present time. Material characterization has been done on L-930 flame retardant woven carbon-epoxy using accelerated testing methodology proposed by Miyano. The material characterization includes: determining the time-temperature shift factor, storage modulus master curve, constant strain rate (CSR) strength master curve, zero stress ratio fatigue strength master curve and fatigue strength at arbitrary load ratio, temperature and frequency for both tensile and shear properties. Several essential tests were performed to fully characterize a composite material: DMA test, constant strain rate (CSR) test at several different temperatures and zero stress ratio fatigue test at several different temperatures. There are evidences showing that accelerated testing methodology cannot be used to predict the shear fatigue strength at arbitrary load ratio but can be used to predict the shear fatigue strength at arbitrary temperature and zero load ratio. It was also found that modulus decay is linear over the log of number of cycles from the beginning until the end of fatigue life and the rate of modulus decay increases as the stress increases. Finite element modelling and analysis were then carried out to predict the static strength and fatigue life of an I-beam structure using the material characterization parameters obtained earlier. A new "stiffness decay model" is introduced. The new model is based on maximum stress and modified Hashin criteria and was implemented in the USDFLD subroutines in conjunction with the finite element models. The static strength and fatigue life of an I-beam composite as well as stiffness decay were predicted and their results agreed very well with the experimental results.